Family functioning profiles and character strengths in young elite athletes from Argentina - Raimundi, M. J.; Molina, M. F.; Schmidt, V.; Hernández-Mendo, A. (International Journal of Sport and Exercise Psychology, 2019)
The goals of this present study were to explore family functioning in terms of cohesion, flexibility, communication, and promotion of challenges in young athletes and to study how family functioning is related to character strengths in elite versus recreational athletes. Adolescents (n = 476) of both genders (56.50% male) between 11 and 19 years old (M = 15.22; SD = 1.50) participated in the study. The elite athletes group (n = 238) was made up of adolescents from youth national teams of different sports from Argentina. The recreational athletes group (n = 238) played sports as an extracurricular activity and were recruited from secondary schools in Buenos Aires. All athletes completed a socio-demographic questionnaire, Parental Promotion of Challenges Scale, Parent-adolescent Communication Inventory, Family Adaptability and Cohesion Evaluation Scale, and Values in Action Inventory for adolescents. A cluster analysis revealed three distinct family functioning profile groups: Cluster 1: positive family functioning (n = 164); Cluster 2: moderate family functioning (n = 215); and Cluster 3: negative family functioning (n = 97). Elite athletes differed from recreational athletes in their family functioning perceptions. A multivariate analysis showed that positive family functioning is related to the development of character strengths in adolescent athletes regardless of whether they are recreational or elite athletes. The results are discussed with regard to the role of family functioning in development opportunities for adolescents to reach their sporting potential and make sports a positive experience.